Bicytopenia Revealing an Intramedullary Spinal Cord Metastatic Prostatic Carcinoma - Marrak, Mehdi; Chaachou, Abdallah; Hedhli, Houssem; Cherni, Nizar; Dridi, Mohamed; Ghozzi, Samir (Archives of Case Reports, 2024)
Usually revealed by lower urinary tract symptoms, prostate neoplasms are the most frequent urological cancer. The patient was a 70-year-old man being explored for bicytopenia in the hematology department: anemia and bicytopenia with no urinary symptoms in the first plan. Bone marrow biopsy was done and the histological and immunohistochemical concluded in an intramedullary spinal cord metastasis of an undifferentiated prostatic carcinoma. We have reviewed the literature one other case of intramedullary metastasis of prostatic cancer was detected but the main symptoms were neurological and the patient was already diagnosed with his cancer.